Exercise as an Aging Mimetic: A New Perspective on the Mechanisms Behind Exercise as Preventive Medicine Against Age-Related Chronic Disease - Lefferts, Wesley K.; Davis, Mary M.; Valentine, Rudy J. (Frontiers in Physiology, 2022)
Age-related chronic diseases are among the most common causes of mortality and account for a majority of global disease burden. Preventative lifestyle behaviors, such as regular exercise, play a critical role in attenuating chronic disease burden. However, the exact mechanism behind exercise as a form of preventative medicine remains poorly defined. Interestingly, many of the physiological responses to exercise are comparable to aging. This paper explores an overarching hypothesis that exercise protects against aging/age-related chronic disease because the physiological stress of exercise mimics aging. Acute exercise transiently disrupts cardiovascular, musculoskeletal, and brain function and triggers a substantial inflammatory response in a manner that mimics aging/age-related chronic disease. Data indicate that select acute exercise responses may be similar in magnitude to changes seen with +10-50 years of aging. The initial insult of the age-mimicking effects of exercise induces beneficial adaptations that serve to attenuate disruption to successive “aging” stimuli (i.e. exercise). Ultimately, these exercise-induced adaptations reduce the subsequent physiological stress incurred from aging and protect against age-related chronic disease. To further examine this hypothesis, future work should more intricately describe the physiological signature of different types/intensities of acute exercise in order to better predict the subsequent adaptation and chronic disease prevention with exercise training in healthy and at-risk populations.